Endothelial CSN5 impairs NF-κB activation and monocyte adhesion to endothelial cells and is highly expressed in human atherosclerotic lesions - Asare, Yaw; Shagdarsuren, Erdenechimeg; Schmid, Johannes A.; Tilstam, Pathricia V.; Grommes, Jochen; El Bounkari, Omar; Schütz, Anke K.; Weber, Christian; de Winther, Menno P. J.; Noels, Heidi; Bernhagen, Jürgen (Thrombosis and Haemostasis, 2013)
The COP9 signalosome (CSN), a multifunctional protein complex involved in the regulation of cullin-RING-E3 ubiquitin ligases (CRLs), has emerged as a regulator of NF-κB signalling. As NF-κB drives the expression of pro-inflammatory and pro-atherosclerotic genes, we probed the yet unknown role of the CSN, in particular CSN5, on NF-KB-mediated atherogenic responses in endothelial cells. Co-immunoprecipitation in human umbilical vein endothelial cells (HUVECs) revealed the presence of a super-complex between IKK and CSN, which dissociates upon TNF-α stimulation. Furthermore, CSN5 silencing enhanced TNF-α-induced IKB-α degradation and NF-κB activity in luci-ferase reporter assays. This was paralleled by an increased NF-KB-driven upregulation of atherogenic chemokines and adhesion molecules, as measured by qPCR and flow cytometry, and translated into an enhanced arrest of THP-1 monocytes on TNF-α-stimulated, CSN5-depleted HUVECs. Reverse effects on NF-κB activity and THP-1 arrest were seen upon CSN5 overexpression. Finally, double-immunostaining confirmed the expression of CSN subunits in the endothelium of human atherosclerotic lesions, and revealed an increased expression of CSN5 which correlated with atheroprogression. In conclusion, endothelial CSN5 attenuates NF-KB-dependent pro-inflammatory gene expression and monocyte arrest on stimulated endothelial cells in vitro, suggesting that CSN5 might serve as a negative regulator of atherogenesis.Note: The review process for this manuscript was fully handled by G. Y. H. Lip, Editor in Chief.
Keywords: Signal transduction; endothelial cells; cytokines; chemokines; atherosclerosis